Increased leucocyte adhesiveness/aggregation is a most useful indicator of disease activity in patients with inflammatory bowel disease. Issue 1 (July 1995) - Arber, N; Berliner, S; Hallak, A; Bujanover, Y; Dotan, I; Liberman, E; Santo, M; Moshkowitz, M; Ratan, J; Dotan, G
Abstract : The aim of the study was to determine the comparative usefulness of inflammatory markers, in evaluating disease activity in patients with inflammatory bowel disease. Disease activity was assessed by the Mayo Clinic score for ulcerative colitis, and Harvey-Bradshaw score for Crohn's disease. Five hundred normal blood donors who had no underlying inflammatory condition served as controls. The erythrocyte sedimentation rate, platelet and white blood cell count, C reactive protein, and the leucocyte adhesiveness/aggregation test (LAAT) were determined in each patient. One hundred and twenty four patients with inflammatory bowel disease were tested while in remission and 128 in relapse. Their mean (SD) per cent of aggregated white blood cells in the peripheral blood was 8 (5) and 17 (10) respectively compared with controls 6 (4) (p < 0.0001). Moreover, the LAAT could effectively discriminate between various grades of disease activity, the values in patients with active disease being 13 (6)% in mild, 17 (10)% in moderate, and 26 (10)% in severe disease (p < 0.0001). Other acute phase reactants including the erythrocyte sedimentation rate, the white blood cell count, the platelet count, neutrophil count, as well as, the C reactive protein concentration did not differentiate as well between the various groups. Using logistic regression analysis to differentiate between inflammatory bowel disease patients in remission or relapse, the LAAT was the single best indicator. The addition of any other test did not contribute to the discrimination. Among the different laboratory variables tested only the LAAT significantly discriminated between the five different subgroups of controls, remission and mild, moderate or severe disease activity.